2021
DOI: 10.2106/jbjs.21.00345
|View full text |Cite|
|
Sign up to set email alerts
|

Discrepancies in Work-Family Integration Between Female and Male Orthopaedic Surgeons

Abstract: Background: Female surgeons, representing 6.5% of the American Academy of Orthopaedic Surgeons, are particularly vulnerable to work-family conflict. This conflict may deter women from considering orthopaedic surgery as a specialty. The study objective was to identify differences in work-family integration between female and male orthopaedic surgeons in the United States.Methods: An anonymous survey collecting data within the domains of work, family, and satisfaction was completed by 347 orthopaedic surgeons (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Therefore, the focus many need to shift to not only exposure but rather to efforts demonstrating subspecialty appeal. In modern society, female and male orthopaedic surgeons have different expectations for work-family integration, and female physicians are vulnerable to conflicting responsibility with societal and cultural roles 40 . It is imperative that administratively we demonstrate a supportive infrastructure to help navigate unique challenges that may predispose female (as well as URiM ) orthopaedic surgeons to poor work-family integration.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the focus many need to shift to not only exposure but rather to efforts demonstrating subspecialty appeal. In modern society, female and male orthopaedic surgeons have different expectations for work-family integration, and female physicians are vulnerable to conflicting responsibility with societal and cultural roles 40 . It is imperative that administratively we demonstrate a supportive infrastructure to help navigate unique challenges that may predispose female (as well as URiM ) orthopaedic surgeons to poor work-family integration.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary sources of income are less likely for women because industry sponsorship and research grants favor higher-profile physicians, most of whom are men [9,16]. Women orthopaedic surgeons are significantly less likely to perform consulting, be invited as course faculty, or have leadership positions than men orthopaedists [19].…”
Section: Recognition and Rewardmentioning
confidence: 99%
“…Married women doctors with children spent 8.5 hours more on parenting and domestic activities than did their counterparts who were men [15]. Women orthopaedic surgeons are significantly more likely to delay marriage, postpone starting a family, undergo fertility treatments, and take on the majority of parenting compared with men colleagues [19].…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…19 Many of these discrepancies in practice patterns may stem from the greater burden placed on women orthopaedic surgeons for parenting and household duties compared with men and misconceptions about the physical demand of certain subspecialties. 20 Women orthopaedic surgeons were less likely to report involvement in courses as faculty, hold academic titles, and consult with industry. In addition, women reported that they required fertility treatment more frequently than men (32.0% vs. 11.9%) and were more likely to defer children until after completion of medical training compared with their male colleagues (63.0% vs. 31.1%).…”
Section: Diversity Among Orthopedic Surgeonsmentioning
confidence: 99%